Bioremediation of propylbenzenes by a novel marine microalga Rhinomonas reticulata S6A isolated from Daya Bay: acute toxicity, growth kinetics and biodegradation performance - Du, Shuhao; Cui, Jiali; Meng, Fanping; Li, Haiping; Cui, Hongwu; Xia, Yufan (Frontiers in Marine Science, 2023)
This study investigated the degradation characteristics of propylbenzenes (PBZs, including isopropylbenzene and n-propylbenzene), with high leakage risks and ecological hazards, by a newly isolated marine microalga named Rhinomonas reticulata S6A which is a promising candidate for eco-friendly bioremediation from marine. About 72% and 56% of n-PBZ and i-PBZ can be degraded after 7 days in culture. The acute toxicity of n-PBZ (96h - EC50 = 2.38 mg/L) was higher than that of i-PBZ (96h - EC50 = 3.65 mg/L). The growth inhibition kinetics of this strain were consistent with the Edwards model (R2 = 0.998) and Aiba model (R2 = 0.999). The optimal concentrations for the degradation of n-PBZ and i-PBZ were calculated to be 2.42 mg/L and 2.78 mg/L, respectively. The degradation trends of PBZs conformed to the zero-order kinetic model, and k increased with initial concentrations. The moderate increase in inoculation density could accelerate the degradation of PBZs, with the maximum specific growth rates (r) of 1.116/d (n-PBZ) and 1.230/d (i-PBZ) at the initial inoculation density of 104 cells/mL, while over-inoculation (initial microalgae density more than 105 cells/mL) was not conducive to the degradation of the pollutants. There is not much data on the biodegradation of PBZs in the aquatic environment, so it would be worthwhile to try to apply the new microalgae to explore the fate of PBZs.